Public sector work intensification and negative behaviors. Issue 4 (13th July 2015) - Omari, Maryam; Paull, Megan
Abstract : Purpose: – The purpose of this paper is to explore issues associated with sector specific change in the Australian Public Service (APS). Evidence is presented on the impact of New Public Management (NPM) on work intensification and subsequent negative behaviors by giving voice to APS employees who were subject to the NPM changes. Design/methodology/approach: – Data were collected from APS employees, human resource managers and policy makers across 11 agencies on the nature of the changes, context of work, and workplace interactions. The study adopted a triangulated mixed method interpretivist approach using a survey instrument, stories, focus groups, and interviews. Findings: – The NPM changes were aimed at creating a more professional and accountable APS. This resulted in individual agencies pursuing different approaches to productivity and efficiency while being accountable to the public and the government within a tight regulatory framework. These changes created competing priorities, affected the nature of the work through intensification, and fueled workplace tensions, thus affecting progress toward the goals of NPM. Practical implications: – The findings of this study will be useful in alerting organizational leaders of possible unintended negative consequences of poorly implemented change programs. Originality/value: – This current study provides evidence that the negative behaviors which arise from the implementation of efficiency focussed change can be damaging to individuals, the nature of work, and therefore organizations and the outcomes sought. Many change management activities in the public sector can lead to negative behaviors if implemented in a way lacking in respect for staff.